HEALTH BENEFITS OF GREEN TEA (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2025)
Annotation. Green tea is a tea made from young, unripe leaves of the tea plant. It retains its natural color and aroma. The tea leaves are practically not processed, they are only steamed with boiling water. After the steamed leaves are dried, they are rolled into a tube in a special way and sent to tea packaging factories. Green tea is fragrant, quenches thirst well, and is drunk as a decoction as a remedy for some diseases (for example, high blood pressure). This invigorating drink appeared in ancient China several centuries ago. Despite all this time, tea has not lost its importance: it is used for medical and cosmetic purposes, in some countries it is also added to dishes, and, of course, due to its pleasant aroma and taste, it has become a favorite drink of people all over the world. What is the reason for such widespread use of green tea? Harper's Bazaar answers this question by presenting the beneficial properties of this healing elixir.